Diskriminasi Gender terhadap Tokoh Perempuan dalam Novel Penyalin Cahaya Karya Lucia Priandarini - Susilowati, Yani; Abimubarok, Achmad (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2025)
Gender discrimination is still an important issue to be studied in more depth, including the forms of discrimination experienced by a person. The impact of gender discrimination is still large, such as limiting a person's strategic roles due to their status as male or female. In this study, gender discrimination in the form of harassment, restrictions, and exclusion of female characters in the novel is studied in more depth to describe the main factors in order to provide an overview of discriminatory actions. Qualitative methods with content analysis design are used to describe forms of gender discrimination. The data source in this study is the novel Penyalin Cahaya by Lucia Priandarini, the data of which was analyzed using a flow model of analysis. The results of the study show that gender discrimination experienced by female characters consists of sexual harassment, restrictions, and exclusion. The harassment received by female characters in the novel is physical, verbal, visual, and psychological harassment. Then, the restrictions experienced by female characters are especially related to economic restrictions. Finally, the exclusion experienced by female characters is related to function and role.